2010
DOI: 10.1242/jeb.048256
|View full text |Cite
|
Sign up to set email alerts
|

The role of serotonin in the enhancement of long-term memory resulting from predator detection in Lymnaea

Abstract: SUMMARYSerotonergic systems play important roles in modulating stress-induced arousal and vigilance behaviours. The pond snail, Lymnaea, shows multiple defensive vigilance behaviours in response to the stress associated with predator detection. Predator detection elicited by crayfish effluent (CE), increases the time to re-emerge from the shell and enhances the shadow withdrawal response. More importantly, in Lymnaea, CE enhances the ability to form long-term memory (LTM). We investigated the role of the serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 92 publications
2
61
0
Order By: Relevance
“…Serotonin is widely present in the animal kingdom, and modulates important behaviours from simple taxis to memory, learning, response to stress, sexual and agonistic behaviour, physiological process (including control of energy balance), circadian rhythms and neurogenesis (Weiger, 1997;Harzsch et al, 1999;Il-Han et al, 2010;Zhang et al, 2011). The role of this biogenic amine in parasite-induced changes in behaviour has been reported in some host-parasite models (Table1) but without elucidation of how the parasite interferes with the host's serotonergic system.…”
Section: Investigating Candidate Neuromodulatory Pathways: Conceptmentioning
confidence: 99%
“…Serotonin is widely present in the animal kingdom, and modulates important behaviours from simple taxis to memory, learning, response to stress, sexual and agonistic behaviour, physiological process (including control of energy balance), circadian rhythms and neurogenesis (Weiger, 1997;Harzsch et al, 1999;Il-Han et al, 2010;Zhang et al, 2011). The role of this biogenic amine in parasite-induced changes in behaviour has been reported in some host-parasite models (Table1) but without elucidation of how the parasite interferes with the host's serotonergic system.…”
Section: Investigating Candidate Neuromodulatory Pathways: Conceptmentioning
confidence: 99%
“…However, since the effects of epicatechin shown here occur within minutes of testing, we do not believe epicatechin works via this mechanism. Finally, we know that although CE, which also enhances LTM formation, works via a serotonergic pathway (Il-Han et al, 2010), blocking this pathway using mianserin (a serotonin receptor antagonist) does not effect the same LTM enhancement induced by epicatechin (Fruson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that a flavonoid, epicatechin, found in dark chocolate, green tea and red wine (Kühnau, 1976;Matsuoka et al, 1995;Galliet al, 2002;Youdim et al, 2002) enhances LTM formation in Lymnaea (Fruson et al, 2012). However, the enhancement brought about by epicatechin occurs via a different mechanism than that brought about by predator detection (Il-Han et al, 2010;Fruson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, our recent results suggest that although the osphradium may play a role in oxygen detection (Wedemeyer & Schild 1995, Kamardin et al 2001, severing the osphradial nerve does not affect aerial respiration during hypoxia when assessed using the number of breathing attempts during training (Il-Han et al 2010, Dalesman et al 2011. We therefore wanted to confirm whether or not severing the osphradial nerve altered basic aerial respiration behaviour.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 94%